Reintrodução na natureza do tamanduá-bandeira (Myrmecophaga tridactyla)após osteossíntese de rádio e ulna - Alves, Carlos Eduardo Fonseca; Carneiro, Candida Mendonca Cunha; Vidotto, Valeria Trombini (My University, 2011)
A female, adult, 27 kg Giant Anteater (Myrmecophaga tridactyla) was directed to the veterinary hospital by the Center ofSelection of Wild Animals (Cetas) of the Brazilian Institute for the Environment and Renewable Natural Resources (Ibama), afterit was found on a highway. After clinical and radiologic examination, radius and ulna fractures of the left thoracic memberwere observed. Taking in consideration to the physical status of the animal, its size, the type of fracture and resources availablein the hospital veterinary, internal fixation with Intramedullary Pinning (on the Radius and Ulna) was the treatment methodchosen. About 35 days after the surgery the animal was walking without difficulties and by x-ray it was possible to observeformation of callus. The presence of decurrent bony deformities due to the type of fixation was not found. As the animal presentedno more difficulties in walking, we opted for its reintroduction to its original environment. The aim of the present casestudy is sharing the results of the Intramedullary Pinning implantation technique, widely used in dogs and cats, now used in a Giant Anteater (Myrmecophaga tridactyla).
Reintroduction in nature of giant anteater (Myrmecophaga tridactyla) after osteosynthesis of radius and ulna.